Medicinal Plants with Acetylcholinesterase Inhibitory Activity: Therapeutic Potential of Brazilian Plants for the Treatment of Alzheimer’s Disease - Oliveira, Fernanda Granja da Silva; Veras, Bruno de Oliveira; Silva, Juliane Maria Dos Santos; Barbosa, Deyzi Caroline da Silva; Silva, Tayane de Cássia Dias Mendes; Amorim, Luciclaudio Cassimiro de; Assis, Caio Rodrigo Dias de; Ramos Ribeiro, Elisabete Regina Fernandes; da Silva, Alexandre Gomes; Silva, Márcia Vanusa da; Almeida, Jackson Roberto Guedes da Silva (Pharmacognosy Reviews)
Alzheimer’s disease (AD) is characterized by persistent impairment of cognitive and psycho motor functions, resulting in reduced short-term memory. In current pharmacotherapy, some available acetylcholinesterase inhibitors (AChEi) have side effects, such as hepatotoxicity. Hence, it is necessary to investigate other sources to obtain compounds inhibiting AChE. In this context, the objective of this study was to review the main publications involving plants collected in Brazil tested for the inhibition of AChE, which may lead to new phytotherapeutic inhibitors. This review was carried out by searching the PubMed, Scopus, and Science Direct databases during September 2018, using several combinations of the following keywords: extract, AChE, Brazil and Alzheimer’s. Inclusion criteria were articles with plant studies col lected in Brazil for the inhibition of AChE (in vivo and/or in vitro), with keywords in the title, abstract, or full text. Articles with studies of purified, synthetic, or semi-synthetic compounds were excluded. In this research, 298 articles were identified and 31 articles were selected. More than forty species of the families Fabaceae, Anacardiaceae, Annonaceae, Malvaceae, Myrtaceae, Arecaceae and Lauraceae were found, and the most cited substances were the phenolic compounds and flavonoids. Alkaloids and steroids were also found in some active plants. The relevance and importance of this work lies in the review of new potential herbal drugs for the treatment of AD, and this survey could collaborate for the development of new medicinal alternatives for this and other neurodegenerative problems related to cerebral avail ability of acetylcholine.
Keywords: Acetylcholinesterase; Alzheimer; Medicinal plants